2020
DOI: 10.1007/s11869-020-00958-9
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in ozone trends under COVID-19 lockdown in a closely located coastal and hillocky metropolis of India

Abstract: The outbreak of COVID-19, a global health challenge faced by countries worldwide, led to a lockdown in India, thereby bringing down the emissions of various air pollutants. Here, we discuss the behaviour of surface ozone (O 3 ) concentrations and its precursors, oxides of nitrogen (NO x ), carbon monoxide (CO), and volatile organic compounds (VOC) at two Indian megacities namely Mumbai and Pune, closely located yet vastly differing in meteorology due to their locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…In a study of PM10 from 2001 to 2019 in Delhi, it was reported that the average concentration of PM10 was 227 µg/m 3 which supports our findings (Sharma et al, 2021b). Korhale et al (2021) reported the concentration of NOx up to 82.1µg/m 3 and the concentration of ozone up to 96.1µg/m 3 which is similar to our findings of air pollutants.…”
Section: Air Quality Around Thermal Power Plantsupporting
confidence: 90%
“…In a study of PM10 from 2001 to 2019 in Delhi, it was reported that the average concentration of PM10 was 227 µg/m 3 which supports our findings (Sharma et al, 2021b). Korhale et al (2021) reported the concentration of NOx up to 82.1µg/m 3 and the concentration of ozone up to 96.1µg/m 3 which is similar to our findings of air pollutants.…”
Section: Air Quality Around Thermal Power Plantsupporting
confidence: 90%
“…The lowest monthly average concentration of CO was reported during April and May 2020 compared to the preceding 3 years of the same month [32]. Studies over western India during the lockdown revealed a plummet of $21% and 25% over Pune and Gujrat respectively, during 2020 in comparison to the same period during 2019, while no significant change is observed at Mumbai [38,62]. Over Bhubaneswar, the eastern coastal city showed a reduction of $14% in CO concentration during complete lockdown period compared to the earlier lockdown period (1st Mar-23rd Mar 2020) whereas it showed a diminution of 11.1% during March-May 2020 compared to the previous year of the same time [18,37].…”
Section: Carbon Monoxide (Co)mentioning
confidence: 84%
“…Some studies revealed concentration of O3 increased by 32% and 6% over Kolkata and Gujarat during the lockdown year as compared to the previous year [34,38]. Likely, an increment of 3% and 2% was observed over Mumbai and Pune respectively during lockdown over the previous year [62]. Similarly, O3 concentration gets amplified by 5.59%, 9.73%, 3.56% during March, April, and May 2020 compared to the same month of 2019.…”
Section: Ozone (O3)mentioning
confidence: 98%
“…Even though O 3 does not decrease by the same proportion as NOx, a reduction in ground level O 3 concentrations is expected with reducing NOx levels. However, evidence of increased tropospheric ozone levels has been reported during lockdown at several places (Korhale et al 2020 ). The increase in concentration of ozone is due to the lower titration of ozone through NO because of the sharp decrease in the concentration of local NOx by road transportation.…”
Section: Changes In No 2 Levelsmentioning
confidence: 99%